2017
DOI: 10.1038/s41559-017-0238-z
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in stomatal function is integral to modelling plant carbon and water fluxes

Abstract: Stomatal pores on leaf surfaces respond to environmental and physiological signals to regulate leaf gas exchange. Mathematical models can predict stomatal conductance (g ), with one parameter (m or g) reflecting the sensitivity of g to the photosynthetic rate (A), atmospheric carbon dioxide concentration and atmospheric humidity, and a second parameter (g) representing the minimum g . Such models are solved iteratively with a photosynthesis model to form the core of many models of crop or ecosystem carbon and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
73
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 47 publications
5
73
0
Order By: Relevance
“…With the observed large inter‐tree‐specific variation in slope parameter, we further showed that accounting for such biotic variation led to improved model estimates of g s (Figure ). This finding is consistent with previous work, which illustrated the diversity in stomatal slope is integral to modelling plant water fluxes (Wolz et al, ). Our results did not show that accounting for the abiotic (e.g.…”
Section: Discussionsupporting
confidence: 94%
“…With the observed large inter‐tree‐specific variation in slope parameter, we further showed that accounting for such biotic variation led to improved model estimates of g s (Figure ). This finding is consistent with previous work, which illustrated the diversity in stomatal slope is integral to modelling plant water fluxes (Wolz et al, ). Our results did not show that accounting for the abiotic (e.g.…”
Section: Discussionsupporting
confidence: 94%
“…While recent work has shown that stomatal regulation and function can vary considerably among temperate trees (Wolz et al 2017), carbon isotope changes in response to drought were remarkably consistent across a diverse group of species and a range of environmental conditions (Fig. 2a).…”
Section: Discussionmentioning
confidence: 69%
“…It is well established that different tree species vary in water use strategies and carbon assimilation based on physiological characteristics (e.g., xylem anatomy, stomatal conductance, and root architecture) and leaf display (e.g., Ford, Hubbard, & Vose, ; Ford, Laseter, Swank, & Vose, ; Pataki & Oren, ; Pataki, Oren, Katul, & Sigmon, ; Vose et al, ; Wolz, Wertin, Abordo, Wang, & Leakey, ). In terms of the regulation of water use, isohydric species such as red maple ( Acer rubrum ) , tulip poplar ( Liriodendron tulipifera ), and evergreen trees with tracheid xylem including loblolly pine ( Pinus taeda ) have relatively high peak water use but reduce transpiration rapidly with decreasing atmospheric humidity to maintain leaf pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Results suggest that the well-known zonation of forest communities over hydrologic gradients is not just a local adaptation but also provides a property that regulates hillslope to catchment-scale behaviour of water use and drought resistance. KEYWORDS carbon cycling, ecohydrologic behaviour, ecosystem resistance, functional organization, water use, watershed 1 | INTRODUCTION It is well established that different tree species vary in water use strategies and carbon assimilation based on physiological characteristics (e.g., xylem anatomy, stomatal conductance, and root architecture) and leaf display (e.g., Ford, Hubbard, & Vose, 2010;Ford, Laseter, Swank, & Vose, 2011;Pataki & Oren, 2003;Pataki, Oren, Katul, & Sigmon, 1998;Wolz, Wertin, Abordo, Wang, & Leakey, 2017). In terms of the regulation of water use, isohydric species such as red maple (Acer rubrum), tulip poplar (Liriodendron tulipifera), and evergreen trees with tracheid xylem including loblolly pine (Pinus taeda) have relatively high peak water use but reduce transpiration rapidly with decreasing atmospheric humidity to maintain leaf pressure.…”
mentioning
confidence: 99%